Applying the Scientific Learning Approach in an Indonesian Kindergarten : A Case from Sarimulyo, Ungaran (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research on the implementation of learning with a scientific approach at Sarimulyo Kindergarten, Ungaran is expected to provide theoretical and practical contributions to early childhood education science. This research is expected to provide basic information for subsequent research. Practically, for early childhood education providers, learning with a scientific approach can be a concern for all school members so that the quality of education provided can be improved. This descriptive qualitative research on learning with a scientific approach was conducted at Sarimulyo Kindergarten. To obtain optimal results, the data collection techniques were observation and interviews, which were then checked for validity before conducting data analysis. The results of the study indicate that Sarimulyo Kindergarten has implemented learning with a scientific approach. Before learning, educators make plans by creating a Lesson Implementation Plan and then implement it. Assessments are carried out authentically by including evidence in the form of photos and videos of learning, in addition to making anecdotal notes, checklists and work results. Educators implement all components of scientific learning, namely observing objects/pictures/photos/videos related to the knowledge to be delivered; asking questions related to the knowledge to be introduced; collecting various information using various media related to the knowledge to be introduced; and associating and communicating knowledge through various children's activities. The recommendation from this study is that learning with a scientific approach at Sarimulyo Kindergarten can serve as a reference for other early childhood education institutions, thereby improving the quality of early childhood education.